Elongated Particles Show a Preferential Uptake in Invasive Cancer Cells - Talya Cohen; Chalom Zemmour; Ora T. Cohen; Ofra Benny (Nanomaterials)
Mechanically driven cellular preference for drug carriers can enhance selectivity in cancer therapy, underscoring the importance of understanding the physical aspects of particle uptake. In this study, it was hypothesized that elongated particles might be preferentially taken up by deformable, aggressive cancer cells compared to normal cells. Two film-stretching methods were tested for 0.8–2.4 μm polystyrene (PS) particles: one based on solubility in organic solvents and the other on heat-induced softening. The heat-induced method produced more homogenous particle batches, with a standard deviation in the particle aspect ratio of 0.42 compared to 0.91 in the solvent-based method. The ability of cells to engulf elongated PS particles versus spherical particles was assessed in two subsets of human melanoma A375 cells. In the more aggressive cancer cell subset (A375+), uptake of elongated PS particles increased by 10% compared to spherical particles. In contrast, the less aggressive subset (A375−) showed a 25% decrease in uptake of elongated particles. This resulted in an uptake ratio between A375+ and A375− that was 1.5 times higher for elongated PS particles than for spherical ones. To further demonstrate relevance to drug delivery, elongated paclitaxel-loaded biodegradable, slow-releasing poly(lactic-co-glycolic) acid (PLGA) particles were synthesized. No significant difference in cytotoxic effect was observed between A375+ and A375− cells treated with spherical drug-loaded particles. However, treatment with ellipsoidal particles led to a significantly enhanced cytotoxic effect in aggressive cells compared to less aggressive cells. These findings present promising directions for tailored cancer drug delivery and demonstrate the importance of particle physical properties in cellular uptake and drug delivery mechanisms.